Effect of annealing temperature on thermoelectric properties of zinc nitride thin films grown by thermal evaporation method. Issue 16 (November 2020) - Zaman, Hassnain; Jacob, Jolly; Mehboob, Khurram; Mahmood, K.; Rehman, U.; Ikram, Salma; Ali, A.; Ashfaq, A.; Amin, N.; Hussain, Sajad; Tanveer, Z.; Ghani, Usman ul
Abstract: In this manuscript, we have successfully grown the Zinc Nitride (Zn3 N2 ) thin films for thermoelectric power generation applications using thermal evaporation method. Zinc powder (0.1 g) was evaporated in vacuum tube furnace on the glass substrate having boot temperature of 830 °C under the nitrogen flow rate of 120 sccm. In order to study the annealing effect, one of samples was annealed at 350 °C using programmable muffle furnace. X-ray diffraction data (XRD) of as grown sample confirm the formation of Zn3 N2 phase while the post annealing resulted in degradation of crystallinity of film. SEM images show the granular morphology, which starts to diffuse upon annealing. Seebeck data has demonstrated the highest value of Seebeck coefficient for as grown sample (142 μV/ ° C) which reduces to 52 μV/ ° C upon annealing. This reduction in Seebeck coefficient was associated with the degradation of crystallinity by post annealing which causes in reduction of the mobility of carriers. Electrical conductivity data show the similar decreasing trend from 83 to 42 S/cm as a result of post annealing. So, overall highest value of Seebeck coefficient and electrical conductivity of un-annealed sample leads to the highest power factor of 1.67 × 10 -4 Wm -1 K -2 .